Effects of Rosmarinus officinalis extract on human primary omental preadipocytes and adipocytes. (July 2015) - Stefanon, Bruno; Pomari, Elena; Colitti, Monica
The prevalence of obesity is increasing all over the world. Although it has been shown that natural substances influence fat metabolism, little is known about the effect on cellular and molecular mechanisms in human. In this in vitro study, the activity of Rosmarinus officinalis (RO) standardized extract in modulating human primary visceral preadipocytes differentiation, lipolysis, and apoptosis was investigated. Moreover, gene expression of key adipogenesis modulators and microRNAs-seq were evaluated. Preadipocytes treated with RO extract significantly reduced triglyceride incorporation during maturation in a dose-dependent manner without affecting cell viability. In addition, RO extract stimulated lipolytic activity in differentiating preadipocytes and mature adipocytes in treated cells compared to controls. Differentiating preadipocytes incubated in the presence of RO extract showed a decreased expression of cell cycle genes such as cyclin D1, cyclin-dependent kinase 4, cyclin-dependent kinase inhibitor 1A (p21, Cip1) and an increased expression of GATA binding protein 3, wingless-type MMTV integration site family, member 3A mRNA levels. Recent studies have demonstrated that some phytochemicals alter the expression of specific genes and microRNAs that play a fundamental role in the pathogenesis of obesity and related diseases. Interestingly, genes modulated in RO-treated cells were found to be validated miRNAs targets, such as let-7f-1, miR-17, and miR-143. The results indicated that RO extract modulates human adipocyte differentiation and significantly interferes with adipogenesis and lipid metabolism, supporting its interest as dietary supplement.